Technology and Job Competence in the Turkish Labor Markets: A Model and Simulations - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
This paper presents system dynamics simulations of the effects of technology on the level of job competence in a subset of the Turkish labor markets. Through deterministic and stochastic simulations, we demonstrate the possibility of considerable technology-induced improvements in the level of job competence. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the 8th International Strategic Management Conference
Keywords: Job competence; technology; labor markets; simulations